Intersubjetividade e interlocução nas relações de causalidade: a funcionalidade dos juntivos causais na língua portuguesa - Neves, Maria Helena de Moura [UNESP] (My University, 2014)
This study approaches the expression of causality in the clause combining in Portuguese, considering, as fundamental, the thread that exists between the performance, in the socio-interaction, and cognitive trigger, based on intersubjectivity. Given that grammar is responsible for the functional organization of those relationships, the study examines the conjunctions traditionally considered as “causal”, especially those constructs invested with effects that go beyond the strict direction cause-consequence. After evaluating the proposal of formation of “causal” conjunction blocks with similar behavior, in contrast with others, we arrive at the discussion of the functional uniqueness of the conjunction porque (because).

Este estudo contempla a expressão da causalidade na junção oracional em português, considerando, na base, o encadeamento que há entre o desempenho de saída, na sociointeração, e o gatilho cognitivo, fincado na intersubjetividade. Estabelecido que a gramática é a responsável pela organização funcional dessas relações, o estudo examina os juntivos tradicionalmente considerados “causais”, contemplando especialmente aquelas construções investidas de efeitos que extrapolam a estrita direção causa-consequência. Avaliadas propostas de formação de blocos de juntivos “causais” de comportamento semelhante, em contraste com outros, chega-se, afinal, à discussão da singularidade funcional da conjunção porque.
Intersubjectivity and interlocution in causal relations: the functionality of causal conjunctions in portuguese
Keywords: Interlocução e intersubjetividade; Causalidade em gramática; Conjunções causais; Interlocução; Intersubjetividade; Causalidade em gramática; Conjunções causais